The Impact of Smart Flying Technologies on Passenger Experience, Operational Efficiency and Sustainable Solutions using XAI - Haridas, Sandhya (Digital Repository of Theses, 2025)
Aviation industry is the foremost of adopting smart and sustainable technologies to enhance passenger experiences, operational efficiency and be future ready. This study critically examines the transformative potential of smart flying and advanced technologies, focusing on their impact on key areas such as real-time baggage tracking, automated immigration systems, AI-based personalization, and operational workflows. Employing a mixed-methods approach, the research integrates quantitative data from 204 survey respondents participating from developing and developed countries, with qualitative insights derived from structured interviews with all personas like passengers, crew, pilots, and airport operations staff from diverse regions worldwide. The study's participants, predominantly from developing and developed nationals, representing key global aviation hubs, provide a comprehensive understanding of the challenges and opportunities associated with these technologies. The findings highlight that 91.7% of participants prioritize digital and sustainable solutions for real-time updates on baggage and dependents' flight statuses, emphasizing the demand for transparency and control during air travel. AI-powered solutions, such as predictive analytics for delays and queue management, were identified as critical in mitigating operational inefficiencies, reducing passenger anxiety, and improving resource allocation. However, challenges persist, including regional disparities in technological infrastructure, language barriers in non-English-speaking countries, and accessibility issues for elderly and digitally inexperienced travelers. Notably, 45.6% of respondents expressed the need for priority check-in services tailored to vulnerable groups, further underscoring the need for inclusive solutions. There are few practical problems passengers face in the name of digitization. That is inconsistent push notifications at irregular intervals by airlines to their passengers regarding the gate changes, flight delays, updates on their baggage. The various channels of communication like their websites, mobile phones, display screens, call centers, etc. is making passenger confused and not sure which is right information and what to follow. In the short window for them to act or enquire, few passengers land up in high stress and anxiety. The study also reveals significant gaps in the global standardization of smart technologies, with fragmented implementation across regions. While passengers in developed markets enjoy access to advanced features like automated immigration and smart baggage tracking, respondents from emerging economies reported limited exposure to such innovations, often citing long wait times, ambiguous procedures, and unresponsive support systems as key pain points. The lack of multilingual interfaces and cultural adaptability further compounds these issues, particularly in international transit hubs where diverse passenger demographics converge. To address these challenges, the research proposes a comprehensive framework to the adoption of smart flying technologies emphasizing the integration of ethical AI to ensure transparency, data privacy, and user inclusivity. Key recommendations include the development of standardized, multilingual platforms for real-time communication and tracking, the implementation of predictive analytics for seamless resource management, and targeted educational initiatives to enhance digital literacy among all age groups. The study also advocates stronger collaboration between aviation stakeholders—including airlines, regulatory bodies, and technology providers—to establish global benchmarks and best practices for smart flying technologies. The theoretical implication of the research lies in its application of Theory of Reasoned Action to understand user acceptance of digital tools, highlighting the interplay between attitudes, subjective norms, and behavioral intentions in shaping adoption patterns. The practical contributions include actionable insights for airlines, airport authorities, and policymakers to optimize passenger experiences while achieving operational efficiency. By addressing critical barriers and proposing scalable solutions, this study lay the groundwork for future research in the digital transformation of the aviation industry, with an emphasis on equity, sustainability, and innovation. This thesis ultimately demonstrates that while smart flying technologies have the potential to revolutionize air travel, their success hinges on inclusive design, cross-regional standardization, and proactive policymaking to ensure equitable benefits for diverse traveler demographics globally. Emphasizing on the need of unified solution and synchronized communication on all channels of broadcasting updates is the goal of this research.